The relationship between online learning self-efficacy and learning engagement: the mediating role of achievement motivation and flow among registered nurses - Zhou, Tong; Chen, Yinhai; Li, Xixi; Yang, Luyao; Zhao, Zhonglei (Frontiers in Psychology, 2025)
IntroductionLearning engagement is a critical predictor of core professional competencies in nursing, yet its influencing factors remain unclear. This study examined the mediating roles of achievement motivation and flow in the relationship between online learning self-efficacy and learning engagement among registered nurses (RNs).MethodsA cross-sectional electronic survey was conducted among 657 RNs from two general hospitals in Sichuan Province, China, between March and May 2024. Participants completed validated instruments, including the Adult Online Learning Self-Efficacy Scale, Achievement Motives Scale (AMS), Educational Flow Scale (EduFlow-2), and Learning Engagement Scale. Descriptive statistics, Pearson correlation, and mediation analysis were conducted using SPSS v29.0. Structural equation modeling was performed using AMOS v24.0.ResultsThe average learning engagement score was 61.55 ± 11.07. Online learning self-efficacy (r = 0.498, p < 0.01), achievement motivation (r = 0.550, p < 0.01), and flow (r = 0.424, p < 0.01) were all positively associated with learning engagement. Achievement motivation (22.2%), flow (24.7%), and their chain effect (11.2%) partially mediated the link between self-efficacy and engagement.DiscussionOnline learning self-efficacy influences RN learning engagement both directly and indirectly, with mediation effects exerted through achievement motivation and flow. These findings highlight the importance of fostering self-efficacy and motivational processes to enhance engagement in online nursing education.